Growth and Nutritional Status of Adolescent School Girls in a Food Insecure Rural Area of Bangladesh: An Anthropometric Perspective - Rahman, Md Azizur (Himalayan Journal of Sociology and Anthropology, 2014)
The present study explored the growth and nutritional status among rural adolescent school girls of food insecure Berasub district of Pabna district in Bangldesh. The study was carried out in rural adolescent school girls of 21 government approved High schools of Berasu district of Pabna district, Bangladesh. Anthropometric and socio-demographic information from 2196 adolescent girls were collected during 2011-2012 academic session. Height and weight were measured using standard procedure and the body mass index (BMI) was calculated. BMI was compared to 2007 WHO growth reference. Height- for-age (HAZ), weight-for-age (WAZ) and BMI-for-age (BMIZ) were used to evaluate stunting, underweight and thinness respectively, based on the National Centre of Heath Statistics (NCHS) < - 2 Z score values. Classification of severity of malnutrition was done based on WHO recommendation. Mean BMI-for-age were less than those of 2007 WHO growth reference for girls at all ages. The overall rate of stunting, underweight and thinness was 33.13%, 28.06% and 17.92% respectively. Based on WHO classification of severity of malnutrition, the overall prevalence of stunting was high (30-39%), whereas those of underweight (≥ 30) and thinness (≥ 15) were very high. The study explores that poor health and nutritional status among the adolescents indicating a major public health problem in food insecure rural areas of Bangladesh. An intensive and comprehensive approach is required to improve the nutritional status of rural adolescent girls of Bangladesh. DOI: http://dx.doi.org/10.3126/hjsa.v6i0.10691 Himalayan Journal of Sociology and Anthropology Vol.6 2014: 103-111